Polymorphisms of ABAT, SCN2A and ALDH5A1 may affect valproic acid responses in the treatment of epilepsy in Chinese. (December 2016) - Li, Xi; Zhang, Jun; Wu, Xi; Yan, Han; Zhang, Yin; He, Ruo-Hui; Tang, Yong-Jun; He, Yi-Jing; Tan, Dan; Mao, Xiao-Yuan; Yin, Ji-Ye; Liu, Zhao-Qian; et al.
Aim: The clinical efficacy of valproic acid (VPA) varies greatly among epileptic patients. To find the potential genetic factors related to VPA responses, the pharmacogenetics study was conducted.Methods: Two hundred and one Chinese Han epileptic patients who were treated by VPA for at least 1 year were recruited. Up to 24 SNPs in 11 candidate genes that correlate with the metabolism, transport or target of VPA were genotyped.Results: Three SNPs, rs1731017 ( ABAT ), rs2304016 ( SCN2A ) and rs1054899 ( ALDH5A1 ) were found associated with VPA responses with the p-values of 0.003, 0.007 and 0.048, respectively. Further interaction analysis showed that the interaction between rs17183814 ( ABAT ) and rs1641022 ( SCN2A ) was also correlated with the response of VPA (p = 0.006).Conclusion: This study found three SNPs and one interaction among ABAT, SCN2A and ALDH5A1 were significantly associated with VPA response, which indicated that these genes may play important roles in the pharmacological mechanism of VPA.